How Does Long-Term Orientation Influence the Investments of Venture Capitals? Evidence From the Organizational Level - Zheng, Tianyi (Frontiers in Psychology, 2022)
Amid great uncertainty along with the possibility of huge returns, venture investment decisions are both technical and artistic. Past studies have paid much attention to the influences of objective factors on venture investment. However, subjective factors have been relatively ignored. As a salient psychological mechanism, temporal focus is of great importance for venture capitalists when making their investment decisions. This study performed content analysis to investigate how temporal focus at the organizational level affects investment decisions of venture capital (VC) firms. The results revealed that VCs with higher level of long-term orientation prefer to invest in less popular industries and ventures in the expansion period. Meanwhile, they are less likely to invest in very new start-ups. Moreover, long-term oriented VCs tend to re-invest in start-ups in their portfolios instead of just shooting once on numerous single start-ups. However, the author did not find any support on preferences of VCs for ventures with high level of human capital.